Balanced life: The impact of hybrid work on employee well-being through the lens of work–family conflict - Junça Silva, A.; Lopes, M. (Employee Relations, 2025)
Purpose Hybrid work is a working model that combines remote or home-based work with in-person work, typically from a traditional location such as an office. Although teleworking has been a model frequently used since the 1990s, it only became more common with the emergence of the COVID-19 pandemic in 2020 and the subsequent mandatory lockdowns. Thus, the post-pandemic era allowed many organizations to adopt a work regime that combines remote and in-person work, namely the hybrid model. In Portugal, this working model is relatively recent and lacks study. Therefore, this study was based on the e-work life model and aimed to test the mediating role of work–family conflict in the relationship between hybrid work and employees’ harmony and mental health. Design/methodology/approach For this purpose, a two-wave survey was conducted with 376 hybrid workers. Findings The results showed that individuals working in a hybrid model tended to experience less work–family conflict, consequently increasing their harmony and mental health. Originality/value The results demonstrate the importance of organizations adopting this working model and using it as a strategy to improve workers’ mental health and well-being.